Peer-assisted HIV partner notification services to strengthen index partner testing for newly diagnosed men who have sex with men in coastal Kenya - Haley Adrian; Maartje Dijkstra; Shally Mahmoud; Khamisi Mohamed; Evans Gichuru; Eduard J. Sanders; Don Operario; Elise M. van der Elst (PLoS ONE, 2025)
Background HIV partner notification services (PNS) have been proven safe and effective in finding undiagnosed HIV infections among general populations in settings with high HIV incidence, but have not been regularly implemented among men who have sex with men in sub-Saharan Africa. This study aimed to describe experiences with PNS in a cohort of newly diagnosed MSM in coastal Kenya, assess facilitators and barriers to participating in PNS, and explore which PNS strategies were preferred for different types of sexual partners. Methods The mixed-method study was conducted between January and July 2019 involving 27 MSM participants newly diagnosed with HIV who participated in PNS, of which 18 accepted to participate in a semi-structured in-depth interview which captured their perceptions, experiences, and views on PNS. Inductive thematic analysis was used to analyze qualitative data. Results The median age of participants was 28 (interquartile range [IQR] 25–36) years old, and 44.4% completed primary school. The median number of named sexual partners in the previous 12 months was 3 (IQR 2–6; total partners 109). Facilitators to participation in PNS included reassurance of personal safety, support from peer-mobilizers, and a sense of responsibility to others’ well-being to prevent HIV transmission. Barriers to PNS participation included fear of stigma and discrimination as well as missing or incorrect partner contact information. Provider-assisted partner notification was the preferred strategy selected by participants across all types of sexual partners. No participant reported experiencing any IPV or other social harms. Conclusions These findings suggest that PNS, particularly provider-assisted PNS, is a safe and promising HIV testing and linkage strategy for use with MSM in coastal Kenya.